Mortality and Morbidity Patterns of COVID-19 Patients at a Tertiary Health Care Centre of Nepal - Bansal, Prerna; Koirala , Pallavi; Upadhyay, Hari Prasad; Maharjan, Rashmi; Sah, Satish Kumar; Shrestha, Ayasha (Journal of College of Medical Sciences-Nepal, 2022)
Introduction COVID-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) associated with substantial morbidity and mortality putting the entire health system under strain. This study aims to assess the sociodemographic and morbidity factors of COVID-19 patients and their association with COVID-19 mortality. Methods It was an analytical cross-sectional hospital based study in a single tertiary level health care centre in Central part of Nepal. Total 425 COVID-19 patients who were treated at the tertiary health care centre from August 1st 2020 to December 31st 2020 were included in the research. Results Out of 425 patients, 230 (54.1%) were male and 195 (45.9%) were female. The mean age group of patients was 50.01±20.03 years, ranging from 7 days to 91 years of age. Total 262 (61.6%) patients had some type of comorbidity. The deaths were more in advancing age, in males and in patients residing in urban areas. Out of total deaths, 41(85.4%) patients had presence of some type of comorbidity. Age, place of residence, co-morbidities, length of hospital stay and place of treatment of patients showed a significant association with COVID-19 mortality with p-value <0.05. Conclusions COVID-19 mortality risk increases with advancing age and comorbidity. The global morbidity and mortality of the disease can only decline with the combined effect of preventive measures and health promotion of high risk groups especially those with morbidities like diabetes, hypertension and respiratory diseases.